PENGARUH PELATIHAN JUMP SERVICE DENGAN DAN TANPA AWALAN TERHADAP DAYA LEDAK OTOT TUNGKAI - Galih Hari Cahyadi, I Made (Jurnal Ilmu Keolahragaan Undiksha, 2013)
This research aimed to determine the effect of jump service training with the prefix and without the prefik of the leg muscle explosive power. This research type is a quasi-experimental research design with nonrandomized control goup the pre-test post-test design. The subjects were men's students volleyball extracurricular participants in SMA Negeri 1 Selemadeg Tabanan school year 2012/2013 as many as 30 people. Explosive leg muscle power is measured by using a vertical jump test. Data were analyzed by Anava with SPSS 16.0 the results variable leg muscle explosive power to jump service training group with and without the prefix with a significance of 0.000, significance is smaller than α (Sig <0.05), so the research hypothesis " jump service training with and without prefix effect on the increase in leg muscle explosive power "acceptable. And was followed by a further LSD test for comparison, the results of group jump service training with the prefix (6.80) is better than jump service training without the prefik (2.80) to increase leg muscle explosive power. From these results it can be concluded that: (1) jump service with and without the prefix affect the increase in leg muscle explosive power, (2) there is a difference between the effect of jump service training with the prefix and jump service without the prefik to the explosive power of the leg muscles, which jump service training the prefix is ​​better than jump service training without the prefix to increase leg muscle explosive power.